The good tourist, the bad refugee and the ugly German: Xenophobic activities and tourism - Marek Endrich (ZBW - Leibniz Information Centre for Economics, 2020)
This article deals with the economic effects of xenophobic incidents. To analyze these effects, we focus on one important industry, namely tourism. Combining a novel, district-level data set on tourism in Germany with data on xenophobic activities, we find that xenophobic demonstrations lead to a decline in tourism numbers. A media analysis on German newspapers shows that the effect is driven by the media attention towards the incidents. Looking at Dresden as a case study with the Synthetic Control Method provides support for our results. The findings presented here highlight the direct economic costs of xenophobia and strengthen the political case to fight political extremism.
Keywords: F22; L83; 330; Xenophobia; refugees; tourism; district-level data